Induced pain affects auricular and body biosignals: From cold stressor to deep breathing - Rapalis, Andrius; Piartli, Povilas; Jankauskaitė, Lina; Marozas, Vaidotas; Kaniusas, Eugenijus (Frontiers in Physiology, 2023)
Pain affects every fifth adult worldwide and is a significant health problem. From a physiological perspective, pain is a protective reaction that restricts physical functions and causes responses in physiological systems. These responses are accessible for evaluation via recorded biosignals and can be favorably used as feedback in active pain therapy via auricular vagus nerve stimulation (aVNS). The aim of this study is to assess the significance of diverse parameters of biosignals with respect to their deflection from cold stressor to deep breathing and their suitability for use as biofeedback in aVNS stimulator. Seventy-eight volunteers participated in two cold pressors and one deep breathing test. Three targeted physiological parameters (RR interval of electrocardiogram, cardiac deflection magnitude ZAC of ear impedance signal, and cardiac deflection magnitude PPGAC of finger photoplethysmogram) and two reference parameters (systolic and diastolic blood pressures BPS and BPD) were derived and monitored. The results show that the cold water decreases the medians of targeted parameters (by 5.6, 9.3%, and 8.0% of RR, ZAC, and PPGAC, respectively) and increases the medians of reference parameters (by 7.1 and 6.1% of BPS and BPD, respectively), with opposite changes in deep breathing. Increasing pain level from relatively mild to moderate/strong with cold stressor varies the medians of targeted and reference parameters in the range from 0.5 to 6.0% (e.g., 2.9% for RR, ZAC and 6.0% for BPD). The physiological footprints of painful cold stressor and relaxing deep breathing were shown for auricular and non-auricular biosignals. The investigated targeted parameters can be used as biofeedback to close the loop in aVNS to personalize the pain therapy and increase its compliance.